A severe chronic outdoor urban pollution alters some facial aging signs in Chinese women. A tale of two cities. (8th October 2018) - Flament, F.; Bourokba, N.; Nouveau, S.; Li, J.; Charbonneau, A.
Abstract: Background: The impact of a chronic outdoor urban pollution on skin aging‐related facial signs is a poorly referenced topic. Objective: To assess, through visual grading and referential photographic atlas, possible differences in some facial signs between Chinese women, of comparable ages, living in two close cities very differently exposed to urban pollution. Methods: The faces of two cohorts of 204 Chinese women (2 × 102) of same age‐groups (25–45 years), living in Baoding (a highly polluted city) and Dalian (a less polluted city), for at least 15 years, have been analyzed. Standardized facial photographs (full face and lateral views) were taken and examined, focusing on 26 signs that belong to 3 different clusters (wrinkles and skin texture, pigmentation disorders, and skin pores/skin redness). The severity of each facial sign was graded by 15 trained experts with the help of an Asian skin referential photographic Atlas that illustrates various scales of clinical severity (0–5, 0–8…). In addition, a naïve panel of 80 Chinese non‐expert women was asked, while viewing all photographs, to answer to 4 questions regarding skin radiance, dullness, healthy appearance, and perceived age. Results: The increased severity of almost all facial signs was mostly observed in the older group (40–45 years) living in Baoding. In particular, the clinical severity of eight facial signs (five related to skin structure and three related to pigmentation) was found strongly and significantly enhanced by a regular exposure to a severe chronic urban pollution. The naïve panel judged the facial appearance of women from Baoding less radiant, duller, less healthy, and found them older than their Dalian counterparts. The monthly‐recorded weather conditions (UV radiance, temperature, wind, precipitations) of the two cities (of same latitude) show that these only differ by their very different Air Quality Indexes (AQI). The daily life conditions of all women (UV exposure, use of cosmetic facial products, intake of sweet or spicy food…) were found similar in all age‐groups. Conclusion: As compared to a moderately polluted region, a severe chronic outdoor urban pollution favors the aggravation of some facial signs in Chinese women. In short, a highly polluted environment can be viewed as an additional accelerating factor of the skin aging process, when compared to a moderately polluted area. Abstract : Assessments from the naïve panel on full‐face pictures (Mean scores 95% CI) and their differences (D) observed between high and less polluted environments for each age cluster. In red and bold red: highly significant differences.